Perfil epidemiológico e distribuição temporal de leptospirose em Belém do Pará em um período de 10 anos (2010 a 2019) - SOUZA, Emerson Frank Moreira de (2023)
OBJECTIVE: To evaluate the epidemiological profile and the temporal distribution of leptospirosis cases in Belém of Pará in a period between 2010 to 2019. METHODS: This is an ecological, quantitative and descriptive study. Data were collected regarding confirmed cases of leptospirosis notified in Belém-Pa between 2010 and 2019, available in the Notifiable Diseases Information System (SINAN). The Microsoft Office Excel 2019 and BioEstat 5.3 programs were used to perform the quantitative descriptive statistical analyzes and to structure them in spreadsheets, charts and graphs. Subsequently, the data was interpreted according to the objectives. RESULTS: Leptospirosis had a high incidence in Belém (4.61 cases/100 thousand inhab.), Considerably higher than the state (1.49 cases/100 thousand inhab.) And the national (1.80 cases/100 thousand inhab.). As for temporality, it was endemic, due to the uninterrupted annual appearance of cases, and seasonal, due to the periodic increase of cases in rainy periods, especially between January and May. Regarding demographic characteristics, the majority of cases were brown, male, aged between 20 and 39 years old and came from the city of Belém. Regarding the infection environment, the household was the predominant one. Lastly, a considerable mortality rate from leptospirosis (16%) was noted. CONCLUSION: This study demonstrated that leptospirosis is still a notable public health problem in the city of Belém do Pará. The results suggest the need for improvement in basic sanitation services, such as the adequate collection of garbage and the improvement of the drainage system of the city; in addition, implementation of education campaigns aimed at prevention.